Estimating VAT Pass Through - Benedek, Dora (IMF Working Papers; Working Paper, 2015)
This paper estimates the pass through of VAT changes to consumer prices, using a unique dataset providing disaggregated, monthly data on prices and VAT rates for 17 Eurozone countries over 1999-2013. Pass through is much less than full on average, and differs markedly across types of VAT change. For changes in the standard rate, for instance, final pass through is about 100 percent; for reduced rates it is significantly less, at around 30 percent; and for reclassifications it is essentially zero. We also find: differing dynamics of pass through for durables and non-durables; no significant difference in pass through between rate increases and decreases; signs of non-monotonicity in the relationship between pass through and the breadth of the consumption base affected; and indications of significant anticipation effects together with some evidence of lagged effects in the two years around reform. The results are robust against endogeneity and attenuation bias.